Inklusivitas & Layanan Anak Berkebutuhan Khusus - Nuraini Nuraini; Zahra Atiah; Azizah Hanum OK (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2026)
For every child to receive an equal education, inclusive education at the early childhood education (PAUD) level is a strategic step. The purpose of this study is to thoroughly study the basic concepts of inclusive education in early childhood, identify various types of specific challenges for Children with Special Needs (ABK) in regular classes, and evaluate how effective the use of inclusive learning methods is in optimizing child development. This study uses a literature review with a descriptive qualitative approach. Secondary data were analyzed using content analysis. According to the study, teachers in regular classes face multidimensional characteristics of ABK. These obstacles include visual impairment, deafness, mental retardation, physical disability, emotional retardation/ADHD, autism, and exceptional intelligence. To overcome these problems, it has been proven that the use of assistive technology, a more flexible curriculum, individualized learning programs (IPC) based on initial assessment, varied teaching methods, and a friendly environment can be helpful. This study shows that teachers are not the only key to the success of inclusive education. This requires strong multi-stakeholder collaboration between the government, schools, special education teachers (GPK), professionals, and parents to address facility challenges and eliminate existing stigma in the field.